ANALISIS PENGARUH LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP KEMAMPUAN PENGELOLAAN KEUANGAN PRIBADI PADA GENERASI Z DI DESA SINDANGMULYA - Safitri, Nimas; Suryati, Adelina; Sumardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology has transformed the financial behavior of society, particularly Generation Z, who have broad access to various digital financial services such as e-wallets, buy-now-pay-later (BNPL) facilities, and online lending. While these services offer convenience, they also increase the risk of consumptive behavior if not supported by sound personal financial management skills. Low financial literacy and a consumptive lifestyle are considered key factors influencing Generation Z's ability to manage their personal finances. Therefore, this study aims to analyze the partial and simultaneous effects of financial literacy and lifestyle on personal financial management capability among Generation Z in Sindangmulya Village. The study is based on the Theory of Planned Behavior proposed by Ajzen (1991). A quantitative approach with an associative research design was employed. The sample consisted of 90 respondents selected using purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using IBM SPSS Statistics version 27, including descriptive statistics, validity and reliability tests, classical assumption tests, multiple linear regression, correlation analysis, coefficient of determination, t-test, and F-test. The findings indicate that financial literacy has a positive and significant effect on personal financial management capability (t = 6.160; p < 0.05), whereas lifestyle has a negative and significant effect (t = -2.604; p < 0.05). Simultaneously, financial literacy and lifestyle significantly influence personal financial management capability (F = 28.522; p < 0.05). These findings suggest that improving financial literacy enhances personal financial management capability, while a more consumptive lifestyle tends to reduce it. This study is expected to provide valuable insights for the community and policymakers in promoting financial literacy and encouraging more responsible financial behavior among Generation Z.